Korean Clear Speech Improves Speech Intelligibility for Individuals with Normal Hearing and Individuals with Hearing Loss - Shin, Su Yeon; Oh, Hongyeop; Jin, In-Ki (Journal of the American Academy of Audiology, 2020)
Background Clear speech is an effective communication strategy to improve speech intelligibility. While clear speech in several languages has been shown to significantly benefit intelligibility among listeners with differential hearing sensitivities and across environments of different noise levels, whether these results apply to Korean clear speech is unclear on account of the language's unique acoustic and linguistic characteristics.Purpose This study aimed to measure the intelligibility benefits of Korean clear speech relative to those of conversational speech among listeners with normal hearing and hearing loss.Research Design We used a mixed-model design that included both within-subject (effects of speaking style and listening condition) and between-subject (hearing status) elements.Data Collection and Analysis We compared the rationalized arcsine unit scores, which were transformed from the number of keywords recognized and repeated, between clear and conversational speech in groups with different hearing sensitivities across five listening conditions (quiet and 10, 5, 0, and –5 dB signal-to-noise ratio) using a mixed model analysis.Results The intelligibility scores of Korean clear speech were significantly higher than those of conversational speech under most listening conditions in all groups; the former yielded increases of 6 to 32 rationalized arcsine units in intelligibility.Conclusion The present study provides information on the actual benefits of Korean clear speech for listeners with varying hearing sensitivities. Audiologists or hearing professionals may use this information to establish communication strategies for Korean patients with hearing loss.
Keywords: speech perception; clear speech; communication strategy